2016
DOI: 10.1590/s1677-5538.ibju.2015.0709
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer screening in Brazil: should it be done or not?

Abstract: The use of PSA in the screening, detection and prognosis of prostate cancer (PCa) has revolutionized the diagnosis and treatment of this disorder with an increase in detection rates and PCa organ-confined. Despite these benefits and ease of implementation, tracking PCa remains a matter of great controversy. We conducted a literature review and demographic and epidemiological data in Brazil feeling to assess the current state of screening and whether there is justification for population programs. the differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
(80 reference statements)
0
5
0
Order By: Relevance
“…Silva et al [43] reported an inverse correlation between prostate cancer mortality and deaths by ill-defined causes, thus concluding that the recent improvement of mortality information in poorer regions may have influenced the assessment of trends. The contribution of screening in reducing prostate cancer mortality is uncertain; however, some studies suggested that the screening has no tangible impact at the population level [44, 45]. Braga et al [42] attributed the rise in prostate cancer mortality to the process of population aging and regional disparities in access to healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…Silva et al [43] reported an inverse correlation between prostate cancer mortality and deaths by ill-defined causes, thus concluding that the recent improvement of mortality information in poorer regions may have influenced the assessment of trends. The contribution of screening in reducing prostate cancer mortality is uncertain; however, some studies suggested that the screening has no tangible impact at the population level [44, 45]. Braga et al [42] attributed the rise in prostate cancer mortality to the process of population aging and regional disparities in access to healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…1,24 Nearly half of the Brazilian population presents some degree of African ancestry, which influences PCa epidemiology. 25,26 In our opinion, ethnicity and BMI that showed an influence on rates of post-biopsy complications in our study just pointed to the heterogeneity of our cohort. We considered the low number of patients included a limitation of our study.…”
Section: Discussionmentioning
confidence: 54%
“…35 Researchers disagree about the effectiveness of PSA screening in reducing prostate cancer-related mortality rates; while some studies propose this test as a noninvasive, easy-to-use, early screening tool in the general population, other studies have recommended PSA testing only for those at a high risk for the disease. [36][37][38] An algorithm has been suggested to identify high-risk patients based on their family history, digital rectal examination results and ethnicity. 39 In the current study, while the overall mortality trend was found to have increased over the study period, there was a reduction in certain years, perhaps due to inconsistencies in the data collection.…”
Section: Resultsmentioning
confidence: 99%